DOI: 10.11606/t.10.2008.tde-10042008-155349
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiológico de doenças infecciosas em anatídeos da Fundação Parque Zoológico de São Paulo

Abstract: pelo apoio e liberação, durante todo o período do projeto de doutorado, pelo incentivo e abertura ao aprimoramento científico e profissional.-Ao Prof. Dr. José Soares Ferreira Neto, amigo muito querido e orientador deste trabalho, pela orientação e apoio de sempre, pela amizade, paciência e incentivo durante todo o período dos projetos de Mestrado e Doutorado. Também pela abertura e parceria científicas, em inúmeros trabalhos em conjunto na busca de diagnósticos e condutas na rotina da medicina de animais silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
4
0
4
Order By: Relevance
“…Geese, ducks, mallards, and swans (Order: Anseriformes, Family: Anatidae) can be found in wildlife, zoos, parks, and they can also be raised in captivity for meat production. According to Corrêa (2007), waterfowl housed in the ponds of zoos and public parks are under constant risk of exposure to the pathogens of migratory birds that visit these places during a certain period every year. Monitoring both the animals and the ecosystem in areas where guest visiting occurs frequently is suggested by Chaskda et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geese, ducks, mallards, and swans (Order: Anseriformes, Family: Anatidae) can be found in wildlife, zoos, parks, and they can also be raised in captivity for meat production. According to Corrêa (2007), waterfowl housed in the ponds of zoos and public parks are under constant risk of exposure to the pathogens of migratory birds that visit these places during a certain period every year. Monitoring both the animals and the ecosystem in areas where guest visiting occurs frequently is suggested by Chaskda et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Serological surveys of T. gondii, Sarcocystis sp., and N. caninum in birds in Brazil are scarce, and there is no information about the seroprevalence of these protozoa in geese. Geese maintain contact with humans and migratory birds, and thus can serve as reservoir hosts and vectors of zoonotic pathogens (CORRÊA, 2007;YAN et al, 2011;CONG et al, 2012;VERMA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A high mortality rate was observed in both groups, which may be related to acute clinical and neurological symptoms and to the severity of the disease. This is thought to be reserved in the initial phases and severe in the advanced and neurological phases, where irreversible consequences or animal death may occur (Correa and Correa, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Kim's research findings are interesting because they showed the positive impact of mobile money technology on financial inclusion, yet such technology does not address the fundamental causes of gendered financial inequality or financial exclusion among women. In a related study, Corrêa (2021) argued that Fintech providers have the potential to promote financial inclusion for women despite the existence of social, economic and market barriers for female heads of households and women entrepreneurs and workers. Corrêa's study suggested that gender inequality hinders the accessibility and use financial services despite the developments in technology, science and human rights.…”
Section: Literature Review 21 Literature On Financial Inclusion For S...mentioning
confidence: 99%